2002
DOI: 10.1094/pdis.2002.86.8.897
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Fusarium oxysporum f. sp. melonis Race 1,2 in Muskmelon Lines Nad-1 and Nad-2

Abstract: Of seven doubled-haploid melon lines parthenogenetically originated using irradiated pollen, two lines, Nad-1 and Nad-2, were selected for resistance to Fusarium wilt after successive inoculations with F. oxysporum f. sp. melonis race 1,2w virulent isolate. Nad-1 and Nad-2 were compared with the commercial hybrids and with the parent cvs. Isabelle and Giallo di Paceco. Evaluation of germplasm extended over a 2-year period showed a higher resistance of Nad-1 and Nad-2 plants to Fusarium oxysporum f. sp. melonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…This, together with the fact that most of the resistances to F.o.m race 1,2 are recessive and polygenically controlled (Risser and Rode 1973;Ficcadenti et al 2002) makes difficult its exploitation in breeding programs. Moreover, these accessions could be easily exploited as resistant rootstocks to F.o.m race 1,2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, together with the fact that most of the resistances to F.o.m race 1,2 are recessive and polygenically controlled (Risser and Rode 1973;Ficcadenti et al 2002) makes difficult its exploitation in breeding programs. Moreover, these accessions could be easily exploited as resistant rootstocks to F.o.m race 1,2.…”
Section: Discussionmentioning
confidence: 99%
“…Polygenic recessive genes have been found to confer resistance to race 1,2 in a few Far-Eastern accessions such as 'Ogon 9' and 'Piboule' (Risser and Rode 1973;Perchepied and Pitrat 2004). These accessions allowed breeding of partially resistant lines to race 1,2, such as 'Isabelle' (Risser and Rode 1973), and two doubled-haploid lines, 'Nad-1' and 'Nad-2' (Ficcadenti et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Crown and root rot caused by these fungi are reported (1). The species were isolated from several European countries, Asia, Africa and North America (2). In Iran, for the first time in 1964, the causal agent was isolated from melon in Mashhad (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, partial resistance to race 1.2, under polygenic recessive gene control, has been only found in a few Far-Eastern accessions, such as 'Ogon 9' and 'Kogane Nashi Makuwa' (Risser and Rode 1973;Perchepied and Pitrat 2004), which are organoleptically distant from melons accepted by Western markets. These accessions allowed the development of partially resistant lines to race 1.2, such as 'Isabelle', two doublehaploid lines, 'Nad-1' and 'Nad-2', showing higher levels of resistance than other genotypes (Ficcadenti et al 2002), and 'Dinero', a melon hybrid used in this work. Recently, Herman and Perl-Treves (2007) described a near complete resistance to race 1.2 conferred by two complementary recessive genes in the breeding line ' BIZ', and Oumouloud et al (2009) reported the possible existence of partial resistance to this race in some inodorus accessions of Western origin.…”
Section: Introductionmentioning
confidence: 99%